Marmacuma samimei gen. et sp. nov., (Peracarida; Cumacea; Nannastacidae) from Tarantian (Upper Pleistocene) sediments from the Sea of Marmara, Turkey - Artüz, M. Levent; Sakinç, Mehmet (Zootaxa, 2020)
A new genus and species of Cumacea, Marmacuma samimei gen. et sp. nov., belonging to the family Nannastacidae is described based on the carapace from the core samples taken from several sites in the Sea of Marmara. The new genus differs from others in the family by the ornamentation of its carapace and strong serration on the lower edge. This is the first cumacean species which is detected from the Tarantian (0.126–0.0117 Ma; Upper Pleistocene) sediments of the Sea of Marmara, Turkey.